Economic benefits of high value medicinal plants to Pakistani communities: An analysis of current practice and potential - Sher, Hassan; Aldosari, Ali; Ali, Ahmad; de Boer, Hugo J. (Springer, 2014)
Poverty is pervasive in the Swat Valley, Pakistan. Most of the people survive by farming small landholdings. Many earn additional income by collecting and selling plant material for use in herbal medicine. This material is collected from wild populations but the people involved have little appreciation of the potential value of the plant material they collect and the long term impact their collecting has on local plant populations.In 2012, existing practices in collecting and trading high value minor crops from Swat District, Pakistan, were analyzed. The focus of the study was on the collection pattern of medicinal plants as an economic activity within Swat District and the likely destinations of these products in national or international markets. Local collectors/farmers and dealers were surveyed about their collection efforts, quantities collected, prices received, and resulting incomes. Herbal markets in major cities of Pakistan were surveyed for current market trends, domestic sources of supply, imports and exports of herbal material, price patterns, and market product-quality requirements.It was observed that wild collection is almost the only source of medicinal plant raw material in the country, with virtually no cultivation. Gathering is mostly done by women and children of nomadic Middle Hill tribes who earn supplementary income through this activity, with the plants then brought into the market by collectors who are usually local farmers. The individuals involved in gathering and collecting are largely untrained regarding the pre-harvest and post-harvest treatment of collected material. Most of the collected material is sold to local middlemen. After that, the trade pattern is complex and heterogeneous, involving many players.Pakistan exports of high value plants generate over US$10.5 million annually in 2012, with a substantial percentage of the supply coming from Swat District, but its market share has been declining. Reasons for the decline were identified as unreliable and often poor quality of the material supplied, length of the supply chain, and poor marketing strategies. These problems can be addressed by improving the knowledge of those at the start of the supply chain, improving linkages among all steps in the chain, and developing sustainable harvesting practices.